Contrastive analysis of modern phraseological calques in Polish and Ukrainian - Sosnowski, Wojciech; Tymoshuk, Roman (Papers in Linguistics, 2020)
Borrowing and calquing of phraseological units occupies an important place in the process of enriching contemporary Polish and Ukrainian phraseology. This phenomenon is part of the tendency to internationalize the lexis of the given languages. Both Polish and Ukrainian, being closely related languages, have recently been characterized by increased intensity of the calquing process. In the article, the authors focus on confrontation of accurate and inaccurate language calques using a vast language material coming from national and parallel corpora and other sources.